Pengaruh Model Discovery Learning terhadap Hasil Belajar Tematik Terpadu Tema 8 Kelas V SD - Oktari, Noci; Desyandri, Desyandri (Universitas Negeri Padang, 2021)
This study aims to describe the effect of discovery learning models on integrated themati c learning outcomes on theme 8 in class V in primary schools. This type of research is experimental research using a quantitative approach. The subject of the research was the Va class students and Vb class students with the number of students 38 students of SDN 23 Ujung Gurun, Padang Barat sub- district. the results showed that there was an influence on the use of the model. when administering an experimental class pretest with an average of 37.3 and a standard deviation of 28.97. while in the control class with an average value of 35 and a standard deviation of 26.73. after being given a posttest from the experimental class an average value of 84 with a standard deviation of 80.94 was obtained. while in the control class an average value of 69.2 was obtained with a standard deviation of 136.58.